A case study of student achievement in a secondary charter school. Issue 3 (July 2014) - Hung, Li‐Ching; Badejo, Folashade; Bennett, Jo
Abstract The quality of student learning and achievement in public schools has become a matter of public discourse and policy, thus led to the establishment of charter school concept. However, there are controversial reports on the academic performances of charter schools, inadequate information on their instructional practices, and the learning experiences of students who attend secondary charter schools. The purpose of this case study was to find correlations on instructional practices, learning activities, learner motivation, and their perception of learning at a secondary charter school that serves students in various at‐risk situations that have not been described in existing research. Using a case study, the qualitative research identified instructional practices and connection between motivation, learning, and student's perception of learning. Data collected from 3 administrators, 13 teachers, and 30 students through interviews, observations of classrooms, and observation of social behaviors in the breakfast program, were subjected to inductive analysis. Findings revealed that the secondary charter school utilizes mission‐oriented instructional practices to meet the educational needs of every student. Flexible school structure, rewards, support systems, positive reinforcement, and ardent student teacher relationships were motivating factors responsible for student achievement. Students expressed satisfaction with their learning experiences at the school and able to progress to higher grade levels.